Right under our nose: First nominal record of Inbiomyiidae Buck, 2006 (Diptera) from Brazilian Amazon - Soares, Matheus M. M.; Barros, Luana M.; Rafael, José A. (Entomological Communications, 2024)
We record for the first time a nominal species of Inbiomyiidae Buck, 2006 from the Brazilian Amazon through three male specimens of Inbiomyia matamata Buck, 2006 (Diptera: Inbiomyiidae). The specimens were collected in the municipalities of Borba and Manaus, Amazonas state. In addition, we provide high-resolution photographs of the external morphology and terminalia, and an updated map of geographic distribution of the species.